Legal Regulation of Health Personnel Symposium: Introduction (Washington University Law Quarterly, 1967)
The following three Articles are devoted to an examination of the legal framework of the health services, and its effect upon the adequacy and flexibility of health care delivery systems to meet present and projected needs and demands. If any central focus can be predicated of the whole study, it is this: to what extent does the current legal framework of health care hinder or encourage those innovations which must come to pass if medicine is to keep up with modern needs? More particularly, to what extent does the legal scheme inhibit flexibility in the creation and use of effective health-care manpower? The answers to those questions are, of course, not free from ambiguity and complexity, but it is believed that the following papers contain data without which no answer can even be attempted.
Keywords: Medical jurisprudence